1983
DOI: 10.1002/art.1780261205
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of group a streptococcal cell wall‐induced polyarthritis in the rat comparative studies in arthritis resistant and susceptible inbred rat strains

Abstract: This report addresses the host mechanisms which regulate susceptibility and resistance to group A streptococcal cell wall-induced polyarthritis in the rat. We have compared cell wall tissue distribution and persistence following a single intraperitoneal injection of an aqueous suspension of the cell walls into arthritis susceptible L E W B and resistant F344/N female rats. Selected aspects of the induced inflammatory reaction were also compared. Our results suggest that development of chronic erosive polyarthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 25 publications
3
33
0
Order By: Relevance
“…Chronic, erosive polyarthritis induced by i,p, administration of a single dose of SCW in an aqueous, sterile suspension develops easily in susceptible Lewis rats, whereas most other strains are resistant [1,2,7], The fact that F344 rats are resistant excludes that MHC class I and/or II antigens, and thus epitope selection, are of decisive importance. However, functional T lymphocytes have been shown to play a pivotal role in suseeptibility to SCWinduced, chronic joint inflammation; there even is evidence that SCW-specific T cells are required [3][4][5][6][8][9][10][11]17], Thus, an answer to the question why T cells from F344 rats do not respond to SCW after priming with cell walls might elucidate the mechanism of resistance to SCW arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic, erosive polyarthritis induced by i,p, administration of a single dose of SCW in an aqueous, sterile suspension develops easily in susceptible Lewis rats, whereas most other strains are resistant [1,2,7], The fact that F344 rats are resistant excludes that MHC class I and/or II antigens, and thus epitope selection, are of decisive importance. However, functional T lymphocytes have been shown to play a pivotal role in suseeptibility to SCWinduced, chronic joint inflammation; there even is evidence that SCW-specific T cells are required [3][4][5][6][8][9][10][11]17], Thus, an answer to the question why T cells from F344 rats do not respond to SCW after priming with cell walls might elucidate the mechanism of resistance to SCW arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Dependent on the SCW batch used, either biphasic disease or only the chronic phase may be seen, Thymectomized [3,4], cyclosporin A-treated [4,5] or nude Lewis rats [6], as well as F344 rats [7] are resistant to the second, destructive episode of inflammation, whereas they undergo the acute phase with comparable severity to the Lewis rat. Together, these data strongly suggest an absolute dependence on functional T lymphocytes of the ehronic phase of SCW-induced arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…STOP CSA eighth to the tenth day post-injection (8,14). Beginning between the second and third weeks, nearly 100% of the animals develop an exacerbation of peripheral joint swelling which results in a chronic proliferative and erosive synovitis that persists for months.…”
Section: Days After Injection Scwmentioning
confidence: 99%
“…Histocompatible Fischer (F344/N) rats, on the other hand, do not develop arthritis in response to the same SCW stimulus (1)(2)(3)(4)(5)(6)(7)(8). We previously found that the susceptibility of LEW/N rats to SCW arthritis is related to their defective hypothalamic-pituitary-adrenal (HPA) axis responses to inflammatory and other stress mediators and that the relative SCW arthritis resistance of F344/N rats is related to their intact HPA responses to the same stimuli (9).…”
mentioning
confidence: 99%